HUBUNGAN BIAYA HIDUP DAN PENGELUARAN KONSUMSI MAHASISWA PADA PRODI PENDIDIKAN EKONOMI JURUSAN PIIS FKIPUNIVERSITAS TANJUNGPURA PONTIANAK - Bambang Genjik Sumartono (Jurnal Visi Ilmu Pendidikan, 2023)
Abstractthe title of the research report is the Relationship of Cost of Living and Expenditure of Student Consumption in the Economics study program  of Social science department FKIP of Tanjungpura University.The basis of the research is referring to the income theory that the cost of living provided by parents to students is a fee given periodically can be every month or every year, and is sourced from the income of parents transferred  for limited education costs and the small amount is very dependent. The ability of the student's parents, while the expenditure of student consumption is strongly influenced by the demands of the student's needs in accordance with the consumption pattern that is influenced by the desire to consume or called marginal propencity to consume or MPC.  So referring to the income theory, there is a relationship between the cost of living for students provided by parents and consumption expenditures made for education costs, even the effect not only on consumption but also on student savings, because income will affect consumption and savings that are the needs of students, then student consumption expenditures can be categorized as follows:Student consumption expenditures are less than the cost of living received by studentsStudent consumption expenses are equal to the cost of living received by studentsStudent consumption expenditures are greater than the cost of living received by studentsFurthermore, the problem of this study the author wants to describe the condition of students of economic education programs from the possibility of phenomena above, by survaiing the cost of living and student consumption expenditures in pursuing given by the parents of students and the use of fees carried out by students as a pattern of student consumption expenditure in pursuing education.  The problem of this study is "How to relationship the Cost of Living and Expenditure of Student Consumption in FKIP  Untan Economic Education Program"With the following sub-issues:How diversity of living costs received by students in FKIP Untan economic education study programHow diversity of student consumption expenditure on students of FKIP Untan economic education programHow is there an opportunity to save from the release of its consumption?How the cost of living relationship with student consumption patterns in students of FKIP Untan economic education programHow to relate the cost of living provided by parents with the pattern of spending on savings for educational activities in students of FKIP Untan economic education programHow is the relationship between student consumption patterns and the amount of savings for the purposes of upcoming educationalactivities. And the results can be seen from the description and understanding of the hypothesis. .  Keyword : Relationship of Cost of Living and Expenditure of Student Consumption